Pengaruh Diglosia dalam Menyusun Bahan Ajar Bahasa Sunda serta Tantangan Diglosia terhadap Pencapaian Akademis Siswa - Jelita Maulida Nurhamidah; Adilah Alawiyah; Ichsan Fauzi Rachman (Lembaga Pengembangan Kinerja Dosen, 2024)
This article discusses the influence and challenges of diglossia in language learning on students' academic achievement. Diglossia is expressed as a phenomenon of stable language use because each language is given the freedom to carry out its social functions proportionally. As a phenomenon of using two different language variants in everyday life, of course, diglossia has a significant impact on the educational process. However, people usually do not view diglossia as a problem. This actually makes diglossia a very noteworthy thing, especially in the context of language learning, diglossia creates a gap between the standard language taught in schools and the non-standard language used in daily interactions. This article examines the key challenges faced in addressing the impact of diglossia in language learning, including curriculum mismatches, perceptions of language values, and communication limitations. Efforts to address these challenges require a holistic approach that pays attention to both language variants, strengthens linguistic equity, and promotes a deep understanding of students' language and culture. By understanding the impact and challenges of diglossia in language learning, effective strategies can be devised to improve students' academic achievement and ensure equal access to education for all.